2012
DOI: 10.1016/j.compscitech.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Novel Si/cyanate ester nanocomposites with multifunctional properties

Abstract: Polymer-matrix composites (PMCs) with dispersed Si nanoparticles have been fabricated and investigated for their dielectric and mechanical properties for the first time. It is found that Si nanofillers significantly enhance the dielectric constant of the nanocomposites while preserve the low loss tangent of the Bisphenol E cyanate ester (BECy) matrix. Meanwhile, incorporation of Si nanoparticles effectively stiffens the polymer, as manifested by the large increase in the storage modulus. Furthermore, the AC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
1
19
3
Order By: Relevance
“…The maximum tan δ is still only 0.033 for the specimen with 10 wt.% Si loading, making this material potentially suitable for energy storage. As shown in Table II, however, breakdown strength decreases significantly with respect to the increasing Si loading, which is consistent with a trend observed previously in Si/BECy composites [21]. The reason for this adverse effect may be inhomogeneous dispersion of the Si nanoparticles.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…The maximum tan δ is still only 0.033 for the specimen with 10 wt.% Si loading, making this material potentially suitable for energy storage. As shown in Table II, however, breakdown strength decreases significantly with respect to the increasing Si loading, which is consistent with a trend observed previously in Si/BECy composites [21]. The reason for this adverse effect may be inhomogeneous dispersion of the Si nanoparticles.…”
Section: Introductionsupporting
confidence: 90%
“…It is observed that T g increases slightly as nanofiller loading increases. This observation is different from the T g decrease observed previously in Si/BECy nanocomposites, for increasing Si content [21]. Compared with former studies of metal-oxide-filled nanocomposites, the nanocomposites studied here reveal a similar increase of permittivity [8] and storage modulus [22,23], whereas the slight increase of T g with increased filler loading observed here, was not seen in these former works.…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…It was reported that cyanate esters show good mechanical properties, and this property increases by adding various inorganic additives . Table shows the mechanical properties of the BADCy/nanodiamond composites.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that cyanate esters show good mechanical properties and these properties increase by adding various inorganic additives . Table shows the mechanical properties of the cyanate ester composites.…”
Section: Resultsmentioning
confidence: 99%